Effects of Parental Encouragement on Their Child’s Academic Performance and Poverty Alleviation - Nakamura, Yui (Review of Economic Analysis, 2024)
Parental encouragement improves a child’s academic performance, which reflects the individual accumulation of human capital and can prevent the child from becoming poor in the future. We provide a model to clarify the mechanism by which parental encouragement influences the child’s efforts by considering parental time preference, wages, and background. We find that parents who have a child with low innate ability, high wages, strong time preference, and were given little encouragement from their parents in the past hesitate to encourage their child and tend to give them assistance for survival. We also imply that the influence of parental encouragement to children’s academic performance is strong in early grades rather than in late grades. Moreover, we indicate that educational institutes such as schools and local governments can reduce parents’ time preference and provide information about opportunities that stimulate children's efforts at schools. These actions urge the parents who hesitated to encourage their children to begin to encourage them. Furthermore, these actions increase the effectiveness of parental encouragement and realize the child's efforts at school, which results in improving their wages in the labor market in the future.